(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2022)
Friction stir welding is the most promising high-tech and high-performance process. An important element of this technology is determination of the temperature of the material in the mixing zone, which can be calculated from the amount of heat generated in the friction welding zone by the edge of the rotating tool. This paper presents the results of the author’s experimental study of heat release in spot and linear friction stir welding at different speeds of rotation of the tool and welding speeds. To find this value, the authors of the article chose a scheme of experiments in which the material to be welded – aluminum alloy AMg5 – is modeled in the form of a working tube with a diameter of 20 mm, and a tool made of R6M5 tool steel – in the form of a working plate. In the laboratory of the Industrial Safety Department of FEFU Polytechnic Institute, the authors designed and manufactured two experimental stands for studying the friction moment and specific heat release during spot and linear welding for the experimental tube rotation speeds of 0.4–1.3 m/s (42–105 rad/s) and tool movement speed (welding speed) in the range of 0.42–1.67 mm/s. The dependence of the specific heat release on the linear speed of rotation of the working tube at different welding speeds has an exponential form. In this case, the maximum values and intensity of changes in the specific heat release decrease with increase in the linear speed of rotation of the tool and the respective increase of the welding speed. The obtained results of the specific heat release are generalized in the form of an equation; with the help of which the heat release over the entire area of the end face of the working tool intended for friction stir welding is calculated. At the same time, its different diameters were set at different speeds of its rotation and welding. working tube into the environment.